2022
DOI: 10.1038/s41598-022-11634-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of role of CpG methylation in some epithelial mesenchymal transition gene in a chemoresistant ovarian cancer cell line

Abstract: Ovarian cancer is one of the lethal gynecologic cancers. Chemoresistance is an essential reason for treatment failure and high mortality. Emerging evidence connects epithelial-mesenchymal transition (EMT) like changes and acquisition of chemoresistance in cancers. Including EMT, DNA methylation influences cellular processes. Here, EMT-like changes were investigated in cisplatin-resistant A2780 ovarian cancer cells (A2780cis), wherein role of DNA methylation in some EMT genes regulations was studied. Cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…4 B). The aberrant reactivation of the EMT is a prerequisite for the acquisition of a malignant phenotype in tumor cells, including increased migratory and invasive capabilities, as well as resistance to therapeutic agents [ 29 , 30 ], and reactivation of the EMT also has a complicated relationship with cancer stem cells [ 31 ]. Furthermore, selected genes that have been implicated in EMT and stemness were selected to individually verify their expression patterns via real-time quantitative PCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 B). The aberrant reactivation of the EMT is a prerequisite for the acquisition of a malignant phenotype in tumor cells, including increased migratory and invasive capabilities, as well as resistance to therapeutic agents [ 29 , 30 ], and reactivation of the EMT also has a complicated relationship with cancer stem cells [ 31 ]. Furthermore, selected genes that have been implicated in EMT and stemness were selected to individually verify their expression patterns via real-time quantitative PCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was suggested that DNMT inhibitors might become part of a chemosensitization strategy [ 240 ]. A recently published paper confirmed that EMT genes involved in the metastasis mechanism were regulated by DNA methylation in cisplatin-resistant ovarian cancer cells and, therefore, could be a target of epigenetic-based therapy [ 241 , 242 ]. A significant relationship was reported between promoter methylation of the RAS association domain family protein 1a gene (RASSF1A), one of the tumor suppressor genes, and the risk of ovarian cancer [ 243 ].…”
Section: Egcg Treatment In Malignant Gynecological Diseasesmentioning
confidence: 99%
“…For instance, hypermethylation of ABCB1 and demethylation of the ABCG2 promoter may affect therapeutic efficacy and lead to chemoresistance in ovarian carcinoma, effects attributed to upregulation of P-gp [159,160]. Abnormal methylation of genes involved in the PI3K-AKT, MAPK, and Wnt pathways and in EMT confers resistance on HGSOC cells [161][162][163]. In addition, loss of RAD51C promoter methylation and a low level of BRCA1 methylation have been verified to cause drug resistance.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%